Children's experiences with an intervention aimed to prevent further physical abuse. Issue 1 (16th May 2018) - Thulin, Johanna; Kjellgren, Cecilia; Nilsson, Doris
Abstract: Although many children across cultures are victims of physical abuse, few treatment models target these children and their parents. In Sweden, Combined Parent–Child Cognitive Behavioural Therapy for families at risk for child physical abuse has been successfully used according to pretreatment and posttreatment studies. However, few studies have explored how physically abused children experience treatment. This study includes 20 physically abused children aged 9–17 who completed Combined Parent–Child Cognitive Behavioural Therapy. Children had a positive overall impression of the treatment and highlighted addressing the abuse, as well as processing their experiences as particularly essential. Children described a positive transformation in their family life as a result of treatment, including violence cessation and bonding among family members. Children experienced the intervention as inclusive and child‐friendly. The implications of the promising findings are discussed.